The Effectiveness of the Election Supervisory Body in Realizing Honest and Fair Regional Elections in Nunukan Regency - Jamaluddin; Budiati, Ayuning; Aisyah, Siti (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2025)
This study aims to examine in depth the role and performance of the Election Supervisory Body (Bawaslu) of Nunukan Regency in ensuring that the implementation of the 2020-2023 Regional Head Elections (Pilkada) runs honestly and fairly. The focus of this study lies in Bawaslu's efforts to prevent election violations, resolve election disputes, and increase public participation in the democratic process. Through a qualitative approach, this study uses a data collection method in the form of in-depth interviews with various related parties, including Bawaslu members, election organizers, political parties, election observers, and the community. In addition, a document study was also conducted to obtain relevant secondary data. Data analysis was carried out using thematic analysis techniques to identify patterns, themes, and categories that emerged in the data. The results of the study indicate that in general, the effectiveness of Bawaslu Nunukan Regency in realizing honest and fair Pilkada can be categorized as good. Based on the factors that influence the organization according to Steers (2005), Bawaslu Nunukan Regency has succeeded in building a positive organizational culture, oriented towards results, and focused on public participation. The commitment of the workers to their duties, as well as the support of various related parties, have contributed to this success.